2020
DOI: 10.1161/circoutcomes.119.005902
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Cardiac Rehabilitation Participation and Completion Among Medicare Beneficiaries to Inform the Efforts of a National Initiative

Abstract: Background: Despite cardiac rehabilitation (CR) being shown to improve health outcomes among patients with heart disease, its use has been suboptimal. In response, the Million Hearts Cardiac Rehabilitation Collaborative developed a road map to improve CR use, including increasing participation rates to ≥70% by 2022. This observational study provides current estimates to measure progress and identifies the populations and regions most at risk for CR service underutilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
253
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(293 citation statements)
references
References 40 publications
6
253
2
3
Order By: Relevance
“…Data collected about utilization of medicare benefits to analyse levels of participation, adherence, and completion (>36 sessions) of CR programs revealed higher participation among patients who underwent CABG and PCI after myocardial infraction (MI) when compared to MI alone, with men more than women and age groups of 74 to 85 years. Patients with multiple comorbidities (>5 comorbidities) after cardiac events presented with lower participation [52]. Implementation of CR programs at smaller tertiary hospitals and community centres, awareness about their efficacy, and beneficiaries through medicare would aid in higher participation after coronary revascularization procedures and improve functional parameters like aerobic capacity, physical activity, and quality of life.…”
Section: Prognostic Implications Of Crmentioning
confidence: 99%
“…Data collected about utilization of medicare benefits to analyse levels of participation, adherence, and completion (>36 sessions) of CR programs revealed higher participation among patients who underwent CABG and PCI after myocardial infraction (MI) when compared to MI alone, with men more than women and age groups of 74 to 85 years. Patients with multiple comorbidities (>5 comorbidities) after cardiac events presented with lower participation [52]. Implementation of CR programs at smaller tertiary hospitals and community centres, awareness about their efficacy, and beneficiaries through medicare would aid in higher participation after coronary revascularization procedures and improve functional parameters like aerobic capacity, physical activity, and quality of life.…”
Section: Prognostic Implications Of Crmentioning
confidence: 99%
“…In other cardiac conditions in which the use of cardiac rehabilitation has demonstrated improved health outcomes, participation is low and geographical variability persists in participation. 39 However, hospitals have systematically integrated cardiac rehabilitation orders into their electronic medical record systems to help track the effects on patient outcomes and developed, for example, smart phone access to make adherence easier for patients. 40 Attention in the later years has also been on psychological factors because they can stimulate the autonomic nervous system, triggering the production of catecholamines, increased blood pressure, decreased plasma volume, contraction of coronary arteries, thrombocyte activity, coagulation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite findings that lifestyle interventions and risk factor modification are useful to improve a variety of cardiac patient outcomes, evidence has also shown that the routine use of these interventions is low. 39,52 Patients who had participated in one of the included RCTs in this review described in a qualitative study that participating in the intervention strengthened their belief in their physical capacity and survival; they needed support to move on; and that they had to regain confidence in their mental strength with support from professionals. 11 This review has illustrated knowledge gaps about the most effective lifestyle and risk factor management interventions for patients treated for AF ablation and the specific dose or frequency of these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…An additional explanation can be found in the fact that non-procedure related secondary events as a reason for referral, are often characterized by low participation rates. The secondary events are typical the motivation behind referring HF patients to CR [ 40 ].…”
Section: Discussionmentioning
confidence: 99%